The populist discourse - de Almeida Santos, João (Historia y Comunicación Social, 2023)
This reflection on populism proposes an analysis of the idea of the people throughout history and of the operation of its ideological conversion for purposes of conquest, legitimization, and reproduction of power. A process similar to that of the ideological reconstruction of reality. The populist narrative is an anti-liberal narrative that depreciates the mediation of representative instances since it identifies these instances with the confiscation of the sovereign power of the people by the elites. The unifying power of social heterogeneity is guaranteed by a charismatic figure who interprets popular sentiment and is equivalent to the traditional figure of the monarch, who embodies and interprets the idea of people-nation. Populism (or neo populism) can be from the right or from the left, but both are affirmed by opposition to the liberal matrix of representative democracy.